Pengambilan Keputusan Pemilihan HPLC (Alat Instrumen) Pada Lab. QC Dengan Metode Analitycal Hierarchy Process (AHP) - Sutaarga, Ossa; Aulia, Kiki (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2022)
PT Bio Kusuma Pharmaceutical is a manufacturing company for pharmaceuticals, cosmetics and dietary supplements that was founded in 2003. The company is more engaged in topical medicines and creams for beauty. Increasing the existing market and productivity makes the company prioritize the success of production to increase the company's competitiveness. The increasing demand for products in the market has made PT Bio Kusuma Pharmaceutical have to increase its productivity. However, due to limited testing equipment in the laboratory, it is less effective in meeting the market. From August-October 2019, it showed a delay in testing due to too many batches of production but only one instrument in the laboratory. Production results that are not balanced with demand make the company unable to maximize its productivity due to inadequate testing equipment at the Quality Control laboratory. Based on data on comparison of production and testing in the laboratory where there is a delay in testing due to the inadequacy of the HPLC (High Performance Liquid Chromatography) testing instrument in the Quality Control (QC) laboratory, from this data the company requires additional HPLC (High Performance Liquid Chromatography) instrument tools. From the results of calculations using the AHP (Analytical Hierarchy Process) method, the HPLC (High Performance Liquid Chromatography) instrument from Acquity Arc (Waters) is obtained with a score of 0.46933 with evaluation factors for all criteria and 0.46932 with the ratio of benefits from alternatives.Keywords: Laboratory, HPLC (High Performance Liquid Chromatography), AHP (Analytical Hierarchy Process)